SISTEM KERJA PADA MESIN WINDING MURATEC QPRO EX DALAM PEMBUATAN BENANG - Sukira Sukira; Didik Aribowo (Pusat Penelitian dan Pengabdian Masyarakat, 2025)
This study aims to analyze the working system of the Winding Muratec QPRO EX machine used at PT Budi Texindo Prakarsa. The primary focus of this research is to understand the operational mechanism of the Winding Muratec QPRO EX machine, including the processes of yarn sorting and arrangement, the working principles of the system, and the identification of its main components. In addition, this study also discusses the aspects of maintenance and specific control measures required to ensure optimal machine performance. The research method is an observational approach, conducted by directly observing the yarn winding process using the Winding Muratec QPRO EX machine. Supporting data were obtained through literature studies from relevant journals, articles, and books and documentation methods involving photographs of the observed machine components. The results of this study are expected to provide a deeper understanding of the working system of the Winding Muratec QPRO EX machine and to serve as a reference for operational and maintenance activities within the textile industry